2016
DOI: 10.1093/tropej/fmv092
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Group A Streptococcus Isolated from Throats of Healthy and Symptomatic Children

Abstract: Throat swab cultures must be used in all cases of pharyngitis. Early and appropriate antibiotic therapy will prevent complications. Asymptomatic throat carriage of GAS in children was low in our study. However, they can still act as reservoirs. Emm typing helps in understanding epidemiology and finding new types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
2
1
Order By: Relevance
“…As reported by several studies, all our tested isolates were sensitive to penicillin G (18,28,(31)(32)(33). Hence, penicillin remains the drug of choice for treating GAS infections.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As reported by several studies, all our tested isolates were sensitive to penicillin G (18,28,(31)(32)(33). Hence, penicillin remains the drug of choice for treating GAS infections.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, 9.1% of cases were found resistant to erythromycin, which is lower than the percentage that was found in Brazil, Lebanon, and Spain (15.4%, 10%, and 10.6%, respectively) (18,31,39). This percentage of resistance to erythromycin is higher than the observations of the studies that were done in India, Tunisia, Iran, and Turkey (5.6%, 4.8%, 0%, and 3.8%, respectively) (28,32,33,40). Moreover, the studies conducted in Germany and Italy reported an incremental increase of resistance to erythromycin in GAS strains (24% and 35.8%, respectively) (41,42).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Though the number of female cases are more in this study when compared to male, is not statistically significant. This is similar to the study by Smriti Chauhan et al, (9) .…”
Section: As Seen Insupporting
confidence: 93%
“…8 On the other hand, the nonsuppurative post-streptococcal diseases occur as an autoimmune inflammatory response to GAS infection and affect mainly the heart and the kidney leading to acute rheumatic fever (ARF) and acute glomerulonephritis. 9 ARF follows untreated or inadequately treated GAS throat infection. 10 The incidence of acute rheumatic fever in children aged 5-14 years is 336 500 cases per year, 95% of them occur in less developed countries.…”
Section: Introductionmentioning
confidence: 99%